Peran Hukum Perdata dalam Menjamin Kepastian dan Perlindungan Konsumen - Devi Fitria Wilandari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Consumer protection constitutes a crucial aspect of the modern civil law system, particularly given the unequal position of consumers in comparison to business actors within legal relationships. This study aims to analyze the role of civil law in ensuring legal certainty and consumer protection, especially in the context of contractual relationships between consumers and business actors. The research employs a normative legal method using a statutory approach and a conceptual approach. The data are obtained through library research by examining legislation, legal doctrines, and relevant scholarly journals. The findings indicate that civil law, through regulations governing obligations, contracts, and civil liability, provides a fundamental framework for legal certainty for consumers. However, in practice, the application of the principle of freedom of contract often results in an imbalance of bargaining power due to the widespread use of standard form contracts. Consequently, the Consumer Protection Act plays a significant role in strengthening legal protection by restricting unfair standard clauses and affirming the liability of business actors. This study concludes that civil law and consumer protection legislation complement each other in ensuring legal certainty and substantive justice for consumers, although further improvements in implementation and law enforcement are necessary to enhance the effectiveness of consumer protection.